2003
DOI: 10.1007/bf02491736
|View full text |Cite
|
Sign up to set email alerts
|

Micellar liquid chromatography of polyaromatic hydrocarbons using anionic, cationic, and nonionic surfactants: Armstrong model, LSER interpretation

Abstract: KeyWords Column liquid chromatography Micellar Liquid Chromatography Armstrong Model LinearSolvatTon Energy RelatTonshTp Polyaromatic Hydrocarbons SummaryThe capacity factors kof 28 polyaromatTc hydrocarbons (PAHs) were determTned by micellarlTquTd chromatography (CLM) Tn several mobiles phases containing anTonic (SDS), catTonic (CRAB), or non-Tonic (BrTj 35) surfactants. The mTcelle-water bTndTng constants KMwwere calculated via the Armstrong theory Linear solvation energy relationship (LSER) were used to cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…LSER studies of MBC has shown to have pronounce effect by hydrophobicity as given by high coefficients for "υ" [20]. This type of effect can also be observed in a report by Mutelet et al [15], where υ values for Brij-35 (0.08 M), SDS (0.1 M), and CTAB (0.01 M), with 15% isopropanol as additive are 1.69 ± 0.13, 0.75 ± 0.08, and 0.56 ± 0.08, respectively.…”
Section: Interactions Responsible For Separation Of Isomerssupporting
confidence: 56%
“…LSER studies of MBC has shown to have pronounce effect by hydrophobicity as given by high coefficients for "υ" [20]. This type of effect can also be observed in a report by Mutelet et al [15], where υ values for Brij-35 (0.08 M), SDS (0.1 M), and CTAB (0.01 M), with 15% isopropanol as additive are 1.69 ± 0.13, 0.75 ± 0.08, and 0.56 ± 0.08, respectively.…”
Section: Interactions Responsible For Separation Of Isomerssupporting
confidence: 56%
“…42 In studied condition (at pH 7.0), PAN molecule exists as a mixture of uncharged (~75%) and partly negatively charged (~25%) forms. Considering the critical micelle concentration of CTAB, CMC CTAB = 8.7 × 10 -4 M, 43 at relatively higher concentration of surfactant (in our case 3 × 10 -4 M) added to the solution, the surface micelles are formed on the electrode surface. Therefore, it is expected that adsorption on the electrode surface is mainly maintained by hydrophobic interaction between neutral PAN molecules (~75%) and long hydrophobic tails of CTAB which dominates the coadsorption of PAN with CTAB on PGE surface.…”
Section: Resultsmentioning
confidence: 85%